KESALAHAN MORFOLOGIS DALAM TULISAN IMAJINATIF PEMELAJAR BIPA DI SACRED HEART GIRLS COLLEGE - Derri Ris Riana (UNDAS: Jurnal Hasil Penelitian Bahasa dan Sastra, 2018)
One of the language errors that are still often done by BIPA learners is morphological errors. In fact, morphological mastery is needed to distinguish the class of words and meaning so that the learner is able to place words according to the purpose to be conveyed. The problems in this study are 1) what are morphological errors and changes in meaning arising from morphological contradictions in imaginative writings of BIPA learners in Sacred Heart Girls College and how is the comparison of morphological systems between Indonesian and English. The aims of this study are to reveal morphological errors and changes in meaning arising from morphological contradictions in imaginative writings of BIPA learners in Sacred Heart Girls College and explain the comparison of morphological systems between Indonesian and English. By using qualitative and descriptive methods, the results show that morphological errors are inaccuracies in the use of affixes, especially affix meng- that is often contradicted by other affixes, for example the use affix meng-i and meng-kan, meng- and meng-kan, meng-i and ter-, meng- and ber-, memper- and –an, and meng - and the basic verb in persona passive sentence. These difficulties are caused by differences in the morphological systems of Indonesian and English